Pengaruh Hedonic Shopping Value, Web Informativeness, Web Entertainment Terhadap E-Loyalty Dengan E-Satisfaction Sebagai Mediasi Pada Tokopedia - Ellyta Liska Andriani; Ida Bagus Nyoman Udayana; Nonik Kusuma Ningrum (Master: Jurnal Manajemen dan Bisnis Terapan, 2021)
This research was conducted with in order to identify and analyze the factors that influence loyalty Tokopedia users of online shopping services. With several related variables in this research are hedonic shopping value, web informativeness, web entertainmnet, e-satisfaction, and e-loyalty as dependent variables. The population of this research is tokopedia users, with a sample of 100 tokopedia users. Data collection was done by using a questionnaire method. The test result in this study are that hedonic shopping value has positive effect on e-satisfation, wen informativeness and web entertainmnet have a positive effect on e-satisfaction,  and E-Satisfaction has positive effect on E-Loyalty. Which Means that hypothesis testing is accepted.